Assessing patient risk, benefit and outcomes in drug development: an observational study of regorafenib clinical trials - Matt Vassar; Vinay Prasad; Ryan McIntire; Alyson Haslam; Brody Dennis; Chance Bratten; Griffin K Hughes; Andriana M Peña; Chase Ladd; Brooke Gardner; William Nowlin; Reagan Livingston; et al. (BMJ Oncology)
Objective Our objective of this study was to analyse all oncological clinical trials using regorafenib to create a complete risk/benefit profile for the drug.Background Creating a novel chemotherapy is costly both in time and capital spent for drug manufacturers. To regenerate what they’ve spent, drug manufacturers may attempt to repurpose their medications for new indications via clinical trials. To fully understand the risk/benefits in comparison to a drug’s efficacy, a pooled analysis must be completed.Methods We screened PubMed, Embase, Cochrane (CENTRAL) and ClinicalTrials.gov for trials of regorafenib used to treat solid cancers. Next, we extracted median progression-free survival and overall survival in months, adverse event rates and objective response rate (ORR). Studies were deemed positive, negative or indeterminate based on their pre-specified endpoints and tolerability.Results 56 clinical trials were included in our final sample, with 4960 total participants across 13 indications. Most studies (44 of 56; 78.75%) were non-blinded, and a majority were non-randomised (41 of 56; 73.21%). Trials for colorectal cancer started out as positive but became more negative over time. Cumulative risk to patients increased over time while ORR stayed consistently low.Conclusions Our findings suggest that since regorafenib’s original Food and Drug Administration (FDA) approval, the risk profile for its original indication increased. The amount of non-randomised, single-arm trials in our sample size was concerning, indicating that higher quality research must be conducted. Our results propose that regorafenib’s efficacy and safety may be more impactful in cancers other than its FDA approvals.